EVALUASI PROGRAM PELAYANAN ADMINISTRASI TERPADU (PATEN) DI KANTOR KECAMATAN TANJUNGSIANG KABUPATEN SUBANG - Puspitasari, Neng Lina (JRPA - Journal of Regional Public Administration, 2024)
Evaluation of the sub-district integrated administrative service program (PATEN) is very important for government agencies, because it is to assess the extent of the goals and targets in the sub-district integrated administrative service program (PATEN) in Tanjungsiang sub-district, Subang district. The problem in this research is that the facilities and infrastructure are not yet optimal and there is a lack of socialization regarding integrated sub-district administrative services (PATEN). This research aims to evaluate the sub-district integrated administrative services program (PATEN) at the Tanjungsiang sub-district office, Subang district. According to Anderson in Winarno, the instruments used in this research are implementation and impact. The method used in this research is a qualitative research method. Based on the results of research regarding the evaluation of the sub-district integrated administrative service program (PATEN) at the Tanjungsiang sub-district office, Subang district, the implementation dimension of the sub-district integrated administrative service program (PATEN) can be said to be good, although there are still shortcomings such as inadequate supporting facilities and infrastructure and socialization. which is minimal so that there are still people who do not understand about this integrated sub-district administrative services program (PATEN). Meanwhile, in terms of the impact dimension of the sub-district integrated administrative services program (PATEN), it can be said to be good. Because with the integrated sub-district administrative service program (PATEN) we can provide easy and affordable services for the people of Tanjungsiang sub-district. and all sub-district integrated administrative services (PATEN) provided by Tanjungsiang sub-district are free without any charges for services for the people of Tanjungsiang sub-district, Subang district.